ANALISIS PENERAPAN BIAYA RELEVAN DALAM MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA CV PUTRA JAYA GROUP PAMEKASAN - Zulfa, Amira; Zandra, Rosy Aprieza Puspita (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
This study aims to determine the calculation of the relevant costs made by the company in accepting or rejecting special orders and to analyze the applicability of relevant costs on CV Putra Jaya Group. The object of this research is CV Putra Jaya Group which is located at Jl. Prohibition of Badung. This type of research is descriptive quantitative. The data type is quantitative and qualitative data. Source of data obtained from primary data and secondary data. Data collection techniques is by the method of observation, interview, and documentation. From the results of this study shows that the management of CV Putra Jaya Group has a policy in treating special orders that occur by giving a discount of Rp.150.000 per springbed unit and with consideration of the capacity of idle production. Based on the analysis of the relevant cost indicates that the special order offered by Toko Bima Sakti and Toko Dua Bersaudara is acceptable because the company has profit from the Milky Way Rp. 9.338.672 obtained from the relevant revenues of Rp. 28.000.000 with the relevant cost of Rp. 18.661.328, as well as profit from Toko Dua Brothers Rp. 4,804,804.8 obtained from the relevant revenues of Rp. 21.6 million with the relevant fee of Rp. 16.795.195,2.